LANGUAGE STYLE BETWEEN COMEDIANS FOUND IN THEIR STAND-UP COMEDY PERFORMANCE - Sarah Syafri; Hamzah Hamzah; Rusdi Noor Rosa (Universitas Negeri Padang, 2018)
This study aims to compare language style from stand-up comedian through three level of metafunction. The objects of this research are eight videos, four from each of them on youtube videos.. This study is comperative qualitative with the presence of tables to show the comparison. The result show that they share three similarities and two differences in level Ideational metafunction. In Interpersonal metafunction there are five similarities and four differences. Then, there are four similarities between Daliso and Elon and there are two differencies in textual metafunction. The conclusion of this study there are more similarities rather then differencies, and the differences in style are affected by different cultural ethnic background which are pepresented through speech and lead to the different ways of producing and selection of word in the three level of metafunction.